A tale of two African mongooses (Carnivora: Herpestidae): differing genetic diversity and geographical structure across a continent - (:unkn) unknown (My University, 2022)
Phylogeographies of African mammals reveal patterns that correlate with Pleistocene environmental fluctuations and geographical barriers, which may affect species differently according to their habitat preferences and dispersal capabilities. The marsh mongoose Atilax paludinosus, a widely distributed African carnivoran, is a good model to compare with other African mammals. Here, we aimed to determine if its phylogeographical patterns depend on habitat preferences or other factors, such as dispersal capabilities. One nuclear and two mitochondrial markers were sequenced for marsh mongooses sampled throughout the species range, and sequences were also analysed for another widely distributed African mongoose, the white-tailed mongoose Ichneumia albicauda, previously studied, but more completely for this study. In the marsh mongoose we observed a deep divergence between West + Central Africa and East + South Africa, a pattern also observed in both forest and savanna mammals. With good dispersal capabilities and a preference for riparian habitats, the marsh mongoose may have been confined to forest refugia during Quaternary dry periods and may have used rivers as dispersal corridors. In contrast, in the white-tailed mongoose, the haplogroups were strongly divergent which may indicate more limited dispersal capabilities, but also reflect the preference of this species for more open habitats. These results suggest that life history traits, in addition to habitat preferences, had an impact on how these species were affected by past environmental changes, which is reflected in the geographical genetic structure today.
Keywords: African Research